Antibiotic Essentials: 2017 - Cunha, B. A. Burke A.; Cunha, C. B. Cheston B. (Jaypee Brothers Medical Publishers, 2018)
The new edition of this highly successful annual pocket guide "Antibiotic Essentials" presents clinicians with the most recent information in the field of antimicrobial therapy and infectious diseases. This book comprises of eleven chapters that provide therapeutic recommendations based on the contributors' clinical expertise and experience as well as the literature and clinical guidelines. Written by recognized experts in infectious disease, this edition discusses serum and urinary spectrum summaries of antibiotics and clinically relevant pharmacokinetics. First chapter provides overview of antimicrobial therapy that includes antibiotic selection as well as its dosing. Second chapter discusses empiric therapy for conditions, such as CNS infections, HEENT infections, lower respiratory tract infections, cardiovascular infections, gastrointestinal tract infections, genitourinary tract infections, etc. Third chapter tabulate antibiotic susceptibility profiles and initial therapy of isolates. Fourth chapter highlights parasites, fungi and other unusual organism that inhabits different parts of the body. Fifth chapter describes HIV infection; sixth chapter is on prophylaxis and immunizations; seventh chapter describes pediatric infectious diseases, and chapter eight is chest X-ray atlas. Rest three chapters are on the differential diagnosis of infectious disease; antibiotic pearls & pitfalls, and antimicrobial drug summaries, respectively. Completely new sections on antibiotic stewardship, IV-to-PO switch therapy, and differentiation of colonization and infection, are also included.